Deep Transcranial Magnetic Stimulation for the Treatment of Negative Symptoms in Schizophrenia: Beyond an Antidepressant Effect. Issue 4 (December 2019) - Linsambarth, Sergio; Jeria, Alvaro; Avirame, Keren; Todder, Doron; Riquelme, Raúl; Stehberg, Jimmy
Abstract : Background: Negative symptoms of schizophrenia show limited response to both typical and atypical antipsychotics. Repetitive transcranial magnetic stimulation applied over the prefrontal cortex (PFC) has been proposed as an adjuvant to pharmacological treatment of negative symptoms in schizophrenia, but whether the improvements obtained are specific to negative symptoms or attributable to antidepressant effects is still unclear. Objective: The aim of the present study is to determine to which extent the improvements in negative symptoms of schizophrenia obtained after high-frequency stimulation of the bilateral PFC using deep TMS (dTMS) are attributable to antidepressant effects. Methods: Repetitive dTMS was administered to the PFC in a cohort of 16 patients with schizophrenia under successful pharmacological control of positive symptoms and predominant negative symptoms. Patients were treated using high-frequency (18 Hz) bilateral stimulation applied over the lateral PFC bilaterally using Brainsway H-2 coil. The effects of dTMS on negative symptoms were measured using the Scale for the Assessment of Negative Symptoms and the Positive and Negative Syndrome Scales. We then compared the improvements in negative symptoms obtained in patients showing depressive symptoms (≥7 points) with those found in patients without depression (>7 points), as determined by the Calgary Scale for Depression. Results: Repetitive dTMS treatment induced significant improvements in negative symptoms as assessed using both Scale for the Assessment of Negative Symptoms and Positive and Negative Syndrome Scales. Comparison of the improvements obtained in patients with or without depression at the beginning of treatment revealed similar improvements in negative symptoms, irrespective of subjacent depression. Conclusions: Our data suggest that the beneficial effects of high frequency dTMS of the PFC cannot be attributed solely to its antidepressant effects.